THE CONSTITUTIONAL EMBODIMENT FOR PROTECTING THE PUBLIC LOCATIONS IN THE IRAQI REPUBLIC CONSTITUTION OPERATIVE FOR YEAR 2005 - Gani Zkaier Ateiah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Public areas in Iraq enjoyed important constitutional protection because these public areas are considered as Public National Possessions or that they are owned by the government but they are all used directly by all citizens or that they are considered as public utilities for the country. Hence, rules and texts which organize these locations under the constitution were approved as is clear in Text of Article 27 from the Iraqi Constitution operative in Year 2005 which states as: First: The Public monies are sanctity where protecting them is a duty for each citizen. Second: Organizing through private rules preserves the country's possessions and the limits at which none of these monies are conceded. The constitutional legislator in Iraq made the protection of these public locations a must for the citizens; this is in addition that it is a commitment bourn by the country with all its organizations.